Bayesian network meta-analysis of the impact of exercise therapy on blood glucose in type 2 diabetes patients - Liu, Hairong; Wang, Wenli; Sun, Jing (Frontiers in Endocrinology, 2025)
ObjectiveTo systematically evaluate the effects of exercise therapy on glycemic control in patients with type 2 diabetes mellitus (T2DM) and compare the efficacy of different exercise regimens.MethodsRandomized controlled trials (RCTs) investigating exercise interventions in T2DM were identified through systematic searches of PubMed, The Cochrane Library, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), VIP, Wanfang Database, and China Biology Medicine (CBM) from inception to September 2024. Methodological quality was assessed using the Physiotherapy Evidence Database (PEDro) scale. Data were analyzed using RevMan 5.4, Stata 15.1, R 4.0.5, and JAGS 4.3.0 for Bayesian network meta-analysis.ResultsA total of 22 studies involving 1448 participants were included. All studies were RCTs, with PEDro scores ranging from 6 to 8, with an average score of 6.41, indicating overall high quality. Exercise therapy significantly improved fasting blood glucose (SMD = -0.58, 95%CI: [-0.77, -0.39], P < 0.00001), 2-hour postprandial blood glucose (SMD = -0.51, 95%CI: [-0.73, -0.30], P < 0.00001), and glycated hemoglobin (MD = -0.66, 95%CI: [-0.78, -0.54], P < 0.00001). Aerobic exercise combined with resistance exercise for 14–24 weeks yielded the best improvement in fasting blood glucose (SMD = -2.106, 95%CI: [-3.042, -1.176]), 2-hour postprandial blood glucose (SMD = -3.177, 95%CI: [-5.623, -0.791]), and glycated hemoglobin (MD = -1.382, 95%CI: [-2.050, -0.747]).ConclusionExercise therapy is an effective non-pharmacological approach for improving glycemic control in T2DM. Based on current evidence, combined aerobic and resistance exercise for 14–48 weeks is recommended as the optimal strategy for reducing fasting blood glucose, 2-hour postprandial blood glucose, and glycated hemoglobin levels in this population.Systematic Review Registrationwww.crd.york.ac.uk, identifier CRD420251069226.